The Effect of Audit Quality on Financial Statement Fraud Moderated by Audit Partner Gender - Vicktor Alexander Saroinsong; Hendro Lukman (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the effect of audit quality on financial statement fraud and the moderating role of audit partner gender. Audit quality is proxied by audit tenure, public accounting firm classification, and audit fees, while financial statement fraud is measured using the Fraud Score. This study applies a quantitative approach using secondary data from audited financial statements and annual reports of non-financial companies listed on the Indonesia Stock Exchange during 2021-2025. Based on purposive sampling criteria, 452 companies were selected, resulting in 2,260 firm-year observations. The data were analyzed using panel data regression and Moderated Regression Analysis. The results show that audit tenure has a significant negative effect on financial statement fraud, indicating that longer audit engagement may improve auditors’ understanding of client characteristics and reduce fraud indications. In contrast, public accounting firm classification and audit fees do not significantly affect financial statement fraud. The findings also show that audit partner gender does not moderate the effect of audit tenure, public accounting firm classification, or audit fees on financial statement fraud. In addition, firm size has a significant positive effect, whereas return on assets has no significant effect. These results suggest that audit quality is not determined solely by audit firm reputation or audit fees, but also by auditors’ understanding of clients and the effective implementation of audit procedures.